2014
DOI: 10.1016/j.cemconres.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the carbonation mechanism of CH and C-S-H in terms of kinetics, microstructure changes and moisture properties

Abstract: The purpose of this article is to investigate the carbonation mechanism of CH and C-S-H within type-I cement-based materials in terms of kinetics, microstructure changes and water released from hydrates during carbonation. Carbonation tests were performed under accelerated conditions (10% CO 2 , 25• C and 65± 5% RH). Carbonation profiles were assessed by destructive and non-destructive methods such as phenolphthalein spray test, thermogravimetric analysis, and mercury intrusion porosimetry (destructive), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
285
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(339 citation statements)
references
References 55 publications
15
285
2
5
Order By: Relevance
“…But if considering the carbonation of C-S-H, the effect of the carbonation on the porosity and microstructure of cement paste is still controversial. Carbonation of C-S-H has been studied by many authors (Zdeneˇk Sˇauman 1972, Black, Breen et al 2007, Morandeau, Thiery et al 2014. It agreed that a complex decalcification-polymerization process of the C-S-H and the formation of amorphous silica gel, see equation (2).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…But if considering the carbonation of C-S-H, the effect of the carbonation on the porosity and microstructure of cement paste is still controversial. Carbonation of C-S-H has been studied by many authors (Zdeneˇk Sˇauman 1972, Black, Breen et al 2007, Morandeau, Thiery et al 2014. It agreed that a complex decalcification-polymerization process of the C-S-H and the formation of amorphous silica gel, see equation (2).…”
Section: Introductionmentioning
confidence: 94%
“…From thermodynamic point of view, the carbonation of CH has a priority comparing with C-S-H (Glasser and Matschei 2007). However in experiments the initial rate of carbonation is quite similar (Morandeau, Thiery et al 2014). Therefore, the main carbonation reactions happened inside the concrete are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…In the direct carbonation route steps (1) and (2) occur simultaneously and the rate and extent of carbonation depend on a number of factors such as the precursor composition and moisture saturation degree [24,25], but also on the carbonation conditions such as the CO 2 grade and pressure and the relative humidity [26,27]. Saturation degree and relative humidity play a key role in providing CO 2 access to the connected pore network.…”
Section: Carbonation Mechanismsmentioning
confidence: 99%
“…Data for molar volume of C-S-H is still scarce and it is supposed to be stoichiometry-dependent parameter. Recent experimental study (Morandeau et al 2014) showed that the molar volume of C-S-H is in direct proportion to Ca/Si ratio as:…”
Section: Evolution Of Porosity Due To Carbonationmentioning
confidence: 99%